2021
DOI: 10.1080/21870764.2021.1946268
|View full text |Cite
|
Sign up to set email alerts
|

Pressureless solid-state sintering of SiC ceramics with BN and C additives

Abstract: This study proposes BN as a new sintering aid for pressureless solid-state sintering of SiC ceramics. The full densification of SiC ceramics for 0.5-2.7 wt% BN addition showed the composition tolerance of the newly developed ceramics. The electrical resistivity decreased by an order of magnitude (10 7 →10 6 Ω•cm) as BN content increased from ~0.5 to ~0.9 wt% because of the increased BN-derived B doping in the SiC lattice. A further increase in BN content had no significant effect on the electrical resistivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Prochazka produced 96% relative density of SiC ceramic with additions of 0.5 wt% boron and 1 wt% carbon after sintering at 2050℃ to 2150℃ in an argon atmosphere [8]. The SiC ceramics were fabricated via pressureless solid-state sintering at 2100℃ for 2 h in argon atmosphere with additives, boron nitride as boron source in range of 0.45 wt% to 2.65 wt% and phenolic resin as carbon source [9]. The fabrication of SiC ceramic via pressureless solid-state sintering with boron carbide (B4C) and carbon additives at temperatures between 1950℃ and 2180℃ for 1 h in a vacuum sintering furnace was studied by D. C., et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…Prochazka produced 96% relative density of SiC ceramic with additions of 0.5 wt% boron and 1 wt% carbon after sintering at 2050℃ to 2150℃ in an argon atmosphere [8]. The SiC ceramics were fabricated via pressureless solid-state sintering at 2100℃ for 2 h in argon atmosphere with additives, boron nitride as boron source in range of 0.45 wt% to 2.65 wt% and phenolic resin as carbon source [9]. The fabrication of SiC ceramic via pressureless solid-state sintering with boron carbide (B4C) and carbon additives at temperatures between 1950℃ and 2180℃ for 1 h in a vacuum sintering furnace was studied by D. C., et al [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, addition of B 4 C to SiC without C causes glassy phase formation [25]. Therefore, these two additives should be added together to SiC since studies have shown that SiC produced by solid state sintering has a wide range of uses since SiC sintered by the solid-state method can be produced without losing its superior properties [7,13,17,25,34,35]. Even if SiC is produced using these two additives, the additive ratios must be adjusted well, otherwise SiC with large grain size will be obtained and the elastic modulus and hardness of these SiC will be low [35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the sintering of SiC is complex, requiring a high temperature and pressure to obtain a dense microstructure. For instance, the sintering of SiC through solid-state requires temperatures ≥ 1900 °C [1][2][3][4][5][6][7][8][9][10][11][12][13], whereas liquid-phase sintering requires a temperature range of 1750-1900 °C [14][15][16][17][18][19][20]. Although a dense SiC body can be achieved under such sintering conditions, the microstructure of SiC undergoes coarsening.…”
Section: ■ Introductionmentioning
confidence: 99%